The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.9778/cmajo.20180077
|View full text |Cite
|
Sign up to set email alerts
|

Improved hospital safety performance and reduced medicolegal risk: an ecological study using 2 Canadian databases

Abstract: Background: Few empirical studies have validated the relation between medicolegal risk and hospital patient safety performance. We sought to determine whether there was a relation between in-hospital patient safety events and medicolegal cases involving Canadian physicians. Methods: In this ecological study, we used Poisson regression to compare data from the Canadian Institute for Health Information's Discharge Abstract Database and the database of the Canadian Medical Protective Association (CMPA) of medicol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…[24] Interestingly, only 2.8% of trauma centers had first-hand experience with a video analysisrelated medical-legal problem. Moreso, video review may even reduce medicolegal cases, as Yang et al [29] found a significant relation between patient safety and the risk of medicolegal involvement of physician in Canadian hospitals. In other words, video review may enhance patient safety, which may result in less medicolegal issues of physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Interestingly, only 2.8% of trauma centers had first-hand experience with a video analysisrelated medical-legal problem. Moreso, video review may even reduce medicolegal cases, as Yang et al [29] found a significant relation between patient safety and the risk of medicolegal involvement of physician in Canadian hospitals. In other words, video review may enhance patient safety, which may result in less medicolegal issues of physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are some recently described advanced methods available that could significantly ano[nymize] patients and personnel in the trauma room. In the study by Silas et al (29) videos of operating rooms during surgery were processed into point clouds. Recognition of staff by their colleagues was rated using a Likert scale, where the score of 1 was anonymous, (unable to identify) and a score of 10 was not anonymous, (easy to identify) The mean scores for unaltered and point cloud videos were 7.05 and 1.41, respectively (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The best way to control costs, however, is to improve safety so that both patient harm and subsequent litigation are reduced. Improving safety in health systems overall is likely to reduce the level of avoidable harm and thus decrease litigation111213: the recently published NHS patient safety strategy suggested potential to reduce claims provision by around £750m a year by 2025, for example. The Public Accounts Committee’s 2017 report accordingly recommended that urgent and coordinated action be taken to reduce patient harm, especially in maternity care 4.…”
Section: Reversing the Trendmentioning
confidence: 99%
“…Canadian data support the merits of transition, with evidence demonstrating a reduction of patient safety incidents is associated with reduced physician medicolegal risk. 31 From a physician medicolegal risk management perspective, engagement in programme QI initiatives seems to be a powerful tool against medicolegal liability. Particular to VAR programmes, physicians may perceive increased vulnerability to litigation and patient complaints.…”
Section: Professional Risk Physician Perspectivementioning
confidence: 99%